2013
DOI: 10.1111/acem.12222
|View full text |Cite
|
Sign up to set email alerts
|

Negative Predictive Value of Acetaminophen Concentrations Within Four Hours of Ingestion

Abstract: Objectives: The objective was to ascertain whether acetaminophen (APAP) concentrations less than 100 lg/mL obtained between 1 and 4 hours after acute ingestion accurately predict a nontoxic 4-hour concentration. Methods:The authors performed a multicenter, prospective cohort study involving five emergency departments (EDs) participating in the ToxIC Research Network. Data were collected from May 2009 to December 2011. Patients with APAP concentrations <100 lg/mL drawn between 1 and 4 hours after acute ingestio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…Therefore, it may not be necessary to wait until 4 hours to initiate PAC sampling in a patient to be able to use the Rumack–Matthew nomogram. This contrasts with previous work that explored the ability of one PAC < 100 mg/L between 1 and 4 hours as a predictor of subsequent low concentrations after 4 hours since ingestion (i.e., below the Rumack–Matthew nomogram) . While it was recognized that the reported study was limited by sample size, it was concluded that this method resulted in a proportion of false negatives too high for clinical implementation.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Therefore, it may not be necessary to wait until 4 hours to initiate PAC sampling in a patient to be able to use the Rumack–Matthew nomogram. This contrasts with previous work that explored the ability of one PAC < 100 mg/L between 1 and 4 hours as a predictor of subsequent low concentrations after 4 hours since ingestion (i.e., below the Rumack–Matthew nomogram) . While it was recognized that the reported study was limited by sample size, it was concluded that this method resulted in a proportion of false negatives too high for clinical implementation.…”
Section: Discussionmentioning
confidence: 75%
“…This contrasts with previous work that explored the ability of one PAC < 100 mg/L between 1 and 4 hours as a predictor of subsequent low concentrations after 4 hours since ingestion (i.e., below the Rumack-Matthew nomogram). 20 While it was recognized that the reported study was limited by sample size, it was concluded that this method resulted in a proportion of false negatives too high for clinical implementation. However, prior information provided by the present population PK model and the Bayesian statistical framework has provided a quantitative method for predicting the most likely concentration-time profile that would have arisen in the patient when given one early PAC observation and their prognostic factors.…”
Section: Discussionmentioning
confidence: 99%
“…1 In one single case, serum APAP increased from 58 lg/mL at 90 minutes postingestion to 240 lg/mL at 5 hours. The calculated negative predictive value (NPV) was 98.8% (95% confidence interval [CI] = 93.5% to 99.8%), using a 100 lg/mL cutoff.…”
mentioning
confidence: 88%
“…1 As the authors note, APAP poisoning remains a very common condition; over 130,000 APAP exposures were reported to poison control centers in 2011 alone. 2 Fortunately, the Rumack-Matthew nomogram (plotting serum concentration vs. time after acute ingestion) has long provided clinicians with a useful tool for determining which patients require N-acetylcysteine treatment, based on a single serum APAP concentration.…”
mentioning
confidence: 99%
“…To use this nomogram reliably, the serum levels from 4-24 h post-ingestion should be used. This starting point was chosen because of the initial data available at the time of nomogram production and the possibility of delayed drug absorption [5,6]. On the other hand, acetaminophen is absorbed rapidly and reaches the serum peak level within one hour of the ingestion, suggesting that early serum levels can be predictive of the toxicity [5].…”
Section: Introductionmentioning
confidence: 99%